Предмет: Алгебра,
автор: Ученица2801
Задание внутри
_________________
Приложения:
![](https://files.topotvet.com/i/2d5/2d53b54905069c709beecbd2e11b55e0.png)
Ответы
Автор ответа:
1
7 -4√3 - √3 = 7 -4√3 - √3(√3-2) =7 - 4√3 - 3 + 2√3 =
√3 - 2 √3 - 2 √3 - 2
=4 - 2√3 = 2(2-√3) = -2
√3 -2 -(2 - √3)
√3 - 2 √3 - 2 √3 - 2
=4 - 2√3 = 2(2-√3) = -2
√3 -2 -(2 - √3)
Похожие вопросы
Предмет: Английский язык,
автор: bereketovasuupe
Предмет: Русский язык,
автор: mary9981
Предмет: Русский язык,
автор: krytaya2
Предмет: Литература,
автор: sobirovakholida